Platelet function testing in acute cardiac care – is there a role for prediction or prevention of stent thrombosis and bleeding? - Aradi, Dániel; Collet, Jean-Philippe; Mair, Johannes; Plebani, Mario; Merkely, Béla; Jaffe, Allan S.; Möckel, Martin; Giannitsis, Evangelos; Thygesen, Kristian; ten Berg, Jurrien M.; Mueller, Christian; Storey, Robert F.; Lindahl, Bertil; Huber, Kurt (Thrombosis and Haemostasis, 2015)
The role of platelet function testing in acute coronary syndrome patients undergoing percutaneous coronary intervention remains controversial despite the fact that high platelet reactivity is an independent predictor of stent thrombosis and emerging evidence suggests also a link between low platelet reactivity and bleeding. In this expert opinion paper, the Study Group on Biomarkers in Cardiology of the Acute Cardiovascular Care Association and the Working Group on Thrombosis of the European Society of Cardiology aim to provide an overview of current evidence in this area and recommendations for practicing clinicians.
Keywords: Antiplatelet agents; platelet pharmacology; acute myocardial infarction